Because Water Is Life: Catholic Social Teaching Confronts Earth's Water Crises. By Gary L. Chamberlain. Winona, MN: Anselm Academic, 2018. 188 pages. $21.95 (paper). - McCormick, Patrick T. (Horizons, 2020)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0360966920000237/resource/name/firstPage-S0360966920000237a.jpg